1995
DOI: 10.1001/archpsyc.1995.03950170067009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Caudate Nucleus Volume in Obsessive-compulsive Disorder

Abstract: Our findings provide additional evidence for pathological involvement of the caudate in OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
1
13

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(140 citation statements)
references
References 21 publications
6
120
1
13
Order By: Relevance
“…This may be especially problematic in cases where structural abnormalities and/or increased variability are present. For instance, abnormalities of caudate volume have been inconsistently reported in OCD (see Robinson et al 1995;Rauch and Baxter 1998); resulting mis-registration involving the caudate in the current study could underlie our failure to find significant effects in this region.…”
Section: Discussionmentioning
confidence: 61%
“…This may be especially problematic in cases where structural abnormalities and/or increased variability are present. For instance, abnormalities of caudate volume have been inconsistently reported in OCD (see Robinson et al 1995;Rauch and Baxter 1998); resulting mis-registration involving the caudate in the current study could underlie our failure to find significant effects in this region.…”
Section: Discussionmentioning
confidence: 61%
“…Pediatric OCD is associated with smaller striatum structures (caudate and putamen) (Rosenberg et al 1997b) and a selective deficit in frontostriatal function (Rosenberg et al 1997a) in medication naive subjects. Striatal abnormalities are also seen in adult OCD (Modell et al 1989;Robinson et al 1995). Recently, significantly smaller bilateral orbital frontal and amygdala volumes, as well as a lack of the normal hemispheric asymmetry of the hippocampus-amygdala complex, were found in adult OCD (Szeszko et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the left-side motor symptoms was associated with cleanliness worries, repetitions, and disturbing thoughts, whereas the severity of right-sided symptoms was significantly related only to obsessions with order and routine. Despite the fact that some neuroimaging studies have shown differences between the two hemispheres 25,26,27,28 , evidence regarding lateralized pathophysiology in OCD is inconclusive as yet.…”
Section: Ocd and Parkinson's Diseasementioning
confidence: 99%
“…In addition to anatomic connections, neuroimaging studies have suggested the participation of the basal ganglia in the pathophysiology of OCD. Several studies using both cranial tomography and magnetic resonance imaging have shown the loss of the asymmetry normally observed in caudate nuclei, the left being larger than the right, in patients with OCD or TS 25,26,27,28 . On the other hand, other authors have shown a reduction in size of the lenticular nucleus (globus pallidus and putamen) in magnetic resonance imaging of patients with TS, however without a change in the caudate volume 46,47 .…”
Section: The Basal Ganglia and The Pathophysiology Of Ocdmentioning
confidence: 99%